Hubungan Efisiensi dan Efektifitas dengan Kepuasan Pengguna Sistem Pendukung Keputusan Pemberian Penghargaan Bagi Karyawan Pada Pabrik Plastik "Sukses Mandiri" di Sokaraja Wetan - Carolina Ety Wijayanti; Adhi Wibowo; Suyudi Suyudi; Ary Setyawan (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2020)
Decision Support System for Awarding Employees with the TOPSIS (Technique For Order Preference By Similarity To Ideal Solution) method is applied by the company so that it can assist the leadership in determining which employees are eligible to receive awards based on criteria determined by the company's management, namely: absent, discipline, overtime, years of service and achievements. This study aims to look at the relationship between effectiveness and efficiency on user satisfaction Decision Support System Awarding Award for employees at the Successful Plastic Factory in Sokaraja Wetan, Banyumas. From the tests conducted, it can be concluded that the sig value is obtained. of the Effectiveness of Satisfaction of 0.001 <0.05, this shows that there is a correlation between effectiveness with user satisfaction and efficiency with satisfaction obtained sig. of 0.235> 0.05, this shows that there is no correlation between efficiency and user satisfaction of this decision support system.